An Assessment of Digestibility and Water Stability of a Poultry By-Product Meal (PBM) based diet for Marron (Cherax cainii) - Huynh, Sandra Vi Vi (Curtin University, 2021)
An investigation to optimise the use of poultry by-product meal as a protein replacement in crustacean diets by manipulating drying temperature and feed shape to maximise water stability and protein retention. A standardised method to evaluate aquatic feed has yet to be established. This study presents a series of tools to accurately evaluate aquatic feed performance in the form of optimal feed drying temperature and pellet shape as well as methods to determine digestibility.